Investigation on newsprint paper production from wheat straw and its specification - Afshin Veisi (Regional Information Center for Science and Technology (RICeST), 2015)
In this study, production of bleached chemical- mechanical pulp from wheat straw for newsprint papermaking was investigated. Wheat straw for pulping was obtained from Lorestan province. Wheat straw CMP pulp was prepared at 120, 140, and 160 °C temperature, 45 minute time, 10, 12, and 14% chemicals charge and 10:1 cooking liquor and straw ratio. The yield after defibration treatment varied between 56.5% and 72.5%. Two optimum pulps bleached by TCF method applying 2% and 3% NaOH, 1.5% and 2% H2O2, and 60 and 120 minutes bleaching time. One way analysis variance method showed that bleaching time had the most significant effect on optical properties of handsheet. Applying 3% (based on oven dry weight of the unbleached pulp) NaOH, 2% H2O2, and 120 min. in bleaching improved the brightness and opacity to 52.9%, and 79.5% ISO, respectively. Optimum pulp strengths including tensile, burst and tear indices were measured 43.87 Nm/g, 2.18 kPa.m2/g, and 8.46 mN.m2/g, respectively. All the strengths were higher than newsprint paper strength produced by Mazandaran wood and paper and Korean companies.